Gene Polymorphisms Affecting the Pharmacokinetics and Pharmacodynamics of Donepezil Efficacy - Lu, Jin; Wang, Xiuzhe; Wan, Lili; Fu, Jianliang; Huo, Yan; Zhao, Yuwu; Guo, Cheng (Frontiers in Pharmacology, 2020)
Donepezil (DNP) is the first-line drug used for Alzheimer's disease (AD). However, the therapeutic response rate of patients to DNP varies from 20 to 60%. The main reason for the large differences in the clinical efficacy of DNP therapy is genetic factors, some of which affect pharmacokinetics (PK), while others affect pharmacodynamics (PD). Thus, much emphasis has been placed on the investigation of an association between PK- and PD-related gene polymorphisms and therapeutic response to DNP, but a consistent view does not yet exist. In this review, we summarize recent findings regarding genetic factors influencing the clinical efficacy of DNP, including substantial differences in individual responses as a consequence of polymorphisms in Cytochrome P450 (CYP) 2D6, CY3A4, CY3A5, APOE, ABCA1, ABCB1, ESR1, BCHE, PON-1, CHRNA7, and CHAT. We also discuss possible strategies for the evaluation of the clinical efficacy of DNP, with a specific focus on possible biomarkers of PK/PD parameters, and provide perspectives and limitations within the field, which will also be beneficial for understanding the multiple mechanisms of DNP therapy in AD.